Accrual-Based Accounting Application, Information Technology, HR Competencies, Organizational Commitment on the Financial Statements’ Quality - Ansyori, M. Kholiq; Andesto, Ronny (Interdisciplinary Social Studies, 2022)
Background: Financial statements are the government's primary accountability equipment and sharing data with outsiders and stakeholders to address the extent of the efficiency of the organization's economic resources. Thus, good quality financial statements are needed to increase public confidence and accountability. Aim: This research aims to find out the effect of the accrual-based accounting application, utilization of information technology, human resource competence, and organizational commitment to the quality of financial statements with indicators of budget implementation performance as moderate variables (Satker survey in the Directorate General of Binwasnaker and K3). Method: This study is a quantitative study with census methods of 12 Work Units in the Directorate General of Binwasnaker and K3 as respondents. The tools used in this study used PLS-SEM. The research data used came from answers to questionnaires distributed to respondents. The results of the data assessment and analysis using structural equation modeling with alternative methods partial least square. Findings: Accrual-based accounting, information technology utilization, HR competence have a significant positive effect on the quality of financial statements while organizational commitment does not have a significant positive effect on the quality of financial statements and budget implementation performance indicators do not moderate the relationship of each variable of accrual-based accounting application, utilization of information technology, HR competence and organizational commitment to the quality of financial statements.